Dendritic and Synaptic Degeneration in Pyramidal Neurons of the Sensorimotor Cortex in Neonatal Mice With Kaolin-Induced Hydrocephalus - Femi-Akinlosotu, Omowumi M.; Shokunbi, Matthew T.; Naicker, Thajasvarie (Frontiers in Neuroanatomy, 2019)
Obstructive hydrocephalus is a brain disorder in which circulation of the cerebrospinal fluid (CSF) is altered in a manner that causes expansion of fluid-filled intracranial compartments particularly the ventricles. The pyramidal neurons of the sensorimotor cortex are excitatory in nature and their dendritic spines are target of excitatory synapses. This study evaluated the effect of hydrocephalus on dendritic arborization and synaptic structure of the pyramidal neurons of the sensorymotor cortex of neonatal hydrocephalic mice.. Sterile kaolin suspension (0.01ml of 250mg/mL) was injected intracisternally into day old mice. Control animals mice received sham injections. Pups were weighed and sacrificed on postnatal days (PND) 7, 14, 21. Fixed brain tissue blocks were silver impregnated using a modified golgi staining technique and immunolabelled with synaptophysin to determine dendritic morphology and synaptic integrity respectively Data were analysed using ANOVA at α0.05. Golgi staining revealed diminished arborization of the basal dendrites and loss of dendritic spinesin the pyramidal neurons of hydrocephalic mice. There was significant reduction in the percentage immunoreactivity of anti-synaptophysin in hydrocephalic mice at PND 7 (14.26±1.91%), PND 14 (4.19±1.57%) and PND 21 (17.55±2.76%) compared to age-matched controls (62.57±9.40%, 93.01±1.66% and 99.11±0.63% respectively). These alterations may may impair neuronal connections that are essential for the development of cortical circuits and may contribute to deficits observed in neonatal hydrocephalus.